Robotic Pelvic Lymphadenectomy in Gynecological and Urological Malignancies - Ahmed Eissa; Maria Chiara Sighinolfi; Ibrahim Elsodany; George Habib; Stefano Puliatti; Ahmed Zoeir; Ahmed Elsherbiny; Mohamed Abo-Elenien; Ayman Mousa; Mohamed Elbendary; Mohamed Radwan; Giorgia Gaia; et al. (IMR Press, 2023)
Objectives: Pelvic lymphadenectomy is a crucial step in the management of different pelvic cancers for both prognostic and/or therapeutic goals. Robotic surgeries offered numerous benefits over open and/or laparoscopic surgeries such as better visualization, shorter hospital stay, less pain and better cosmoses. The aim of this narrative review is to evaluate the value and outcomes of robotic pelvic lymph node dissection (PLND). Mechanism: The PubMed database was searched using the following keywords "Robotic" AND "pelvic lymph node dissection" to identify all the relevant articles concerned with the role and outcomes of robotic PLND. We included only English articles published between 2010 and 2022. Data from the retrieved articles were then used to formulate this review that highlight the introduction, the outcomes of robotic pelvic lymph node dissection (PLND), and the mapping of sentinel lymph node (SLN) in cervical, endometrial, prostate, and bladder cancers. Findings in Brief: PLND is an integral part of gynecological and urological oncology for its role in tumor staging and planning of further treatment plan. Furthermore, it may play an important therapeutic role in bladder cancer. Robotic approach to PLND is safe and efficient and can be potentially used for cervical, endometrial, prostate, and bladder cancers. Conclusions: Robotic PLND could be an alternative to open and laparoscopic approaches as it may decrease the associated morbidities without compromising the quality of Lymph node dissection (LND).